Myeloperoxidase-deficient zebrafish show an augmented inflammatory response to challenge with Candida albicans. Issue 1 (May 2015) - Wang, Kun; Fang, Xiao; Ma, Ning; Lin, Qing; Huang, Zhibin; Liu, Wei; Xu, Mengchang; Chen, Xiaohui; Zhang, Wenqing; Zhang, Yiyue
Abstract Myeloperoxidase is a key component of neutrophil granules involved in killing engulfed microorganisms. We obtained a zebrafish mutant (smu681) lacking Sudan black staining by large-scale screening, which was a neutrophil-replete but myeloperoxidase-deficient mutant. When infiltrated with Candida albicans, smu681 embryos and sibling embryos showed similar survival after infection. Proliferation of C. albicans was more rapid in smu681 embryos than in sibling embryos, although it was eventually suppressed. In addition, the number of neutrophils accumulating at the site of infection was significantly larger in mutant embryos than in sibling embryos, and mutant embryos showed increased expression of several inflammatory cytokines after C. albicans infection. These findings indicate that myeloperoxidase deficiency alters the inflammatory response to fungal infection.